The needed daily dose of colchicine in patients with Familial Mediterranean Fever may be higher in women: a study on behalf of the JIR cohort - Ilenia Di Cola; Alessandra Bartoli; Léa Savey; Fatima Bensalek; Marion Delplanque; Rim Bourguiba; Zohra Aknouche; Isabelle Kone-Paut; Linda Rossi-Semerano; Isabelle Melki; Brigitte Bader-Meunier; Bénédicte Neven; et al. (Arthritis Research & Therapy)
Abstract Background At present, there are no data on the relationship between colchicine dose and weight in patients with Familial Mediterranean Fever (FMF). We aimed at describing the daily colchicine dose in a cohort of FMF patients. Methods From 2016 to 2023, a retrospective evaluation of prospectively followed homozygous FMF patients at the French National Reference Centre was performed. Results and conclusions Out of 272 patients, 149 were women (57.8%), with a mean age of 43 years old. The mean weight was 67.8 kg and body mass index 24,2 kg/m². Colchicine was taken by 96% of patients. A subgroup of 30 patients received 2.5 mg/day: they were mostly women (n = 23; 76.7%; p = 0.018), with a lower mean weight (p = 0.019); indeed, 26/30 (87%) weighed < 50 kg. Female sex correlated with higher values of daily colchicine dose (p = 0.0208); weight was not associated with colchicine dose (p = 0.4073). No toxicity has been noted in patients treated with 2.5 mg/day, including patients weighing < 50 kg, and most of these patients were women. We may speculate that the clinical picture of female patients requiring an increased dose of colchicine may be related to the hormonal background, with a possible exaggeration of pyrin activation. This is the first study to examine the question of colchicine dosage in relation to weight of FMF adult patients and to highlight a possible link with female gender. We advise clinicians to explain that colchicine treatment may be used daily up to 2.5 mg without toxicity.